Revitalizing Psychiatric Therapeutics - Hyman, Steven E (Nature Publishing Group, 2014)
Despite high prevalence and enormous unmet medical need, the pharmaceutical industry has recently de-emphasized neuropsychiatric disorders as ‘too difficult' a challenge to warrant major investment. Here I describe major obstacles to drug discovery and development including a lack of new molecular targets, shortcomings of current animal models, and the lack of biomarkers for clinical trials. My major focus, however, is on new technologies and scientific approaches to neuropsychiatric disorders that give promise for revitalizing therapeutics and may thus answer industry's concerns.